2019
DOI: 10.1007/s10067-019-04843-4
|View full text |Cite
|
Sign up to set email alerts
|

What do Australian patients with inflammatory arthritis value in treatment? A discrete choice experiment

Abstract: Background and objectives The purpose of this study was to develop an understanding of treatment preferences in patients with inflammatory arthritis (IA) [rheumatoid arthritis (RA), ankylosing spondylitis (AS) and psoriatic arthritis (PsA)] focussing on treatment attributes that patients' value, their relative importance, and the risk-benefit trade-offs that characterise patients' choices around treatment. Methods A discrete choice experiment (DCE) approach was used. Attributes of interest were clinical effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…Due to differences in nature and characteristics of the disease, the results may not represent the preferences of patients with other types of chronic diseases. Although prior DCEs [44][45][46][47][48] made conclusions that were similar to ours in terms of the relative importance of technology attributes regarding benefits and risks. Future studies need to enrol patients with other diseases and conduct subgroup analyses to identify variations in patients' preferences across different types of diseases.…”
Section: Strengths and Limitationssupporting
confidence: 74%
See 1 more Smart Citation
“…Due to differences in nature and characteristics of the disease, the results may not represent the preferences of patients with other types of chronic diseases. Although prior DCEs [44][45][46][47][48] made conclusions that were similar to ours in terms of the relative importance of technology attributes regarding benefits and risks. Future studies need to enrol patients with other diseases and conduct subgroup analyses to identify variations in patients' preferences across different types of diseases.…”
Section: Strengths and Limitationssupporting
confidence: 74%
“…Comparison with other studies Our findings of patients valuing the effectiveness and safety of medical technologies were consistent with the results by prior studies from other countries which aimed to investigate patients' preferences for the treatment of chronic diseases. [44][45][46][47][48] Our study confirmed that new technologies that could increase health benefits and minimise potential risks were preferred by patients.…”
Section: Summary Of the Findingssupporting
confidence: 70%
“…Treatment attributes mainly included frequency and route of administration either as individual attributes or as a combination. In one study, a labelled experimental design was used, with the treatment profiles indicated as ‘oral’, ‘injection’, ‘infusion’ and an opt out [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Attributes that characterise the degree of certainty around the benefits or risk of treatment were included in two out of three prevention studies [ 45 , 46 ] and one out of two RA treatment studies with general public participants [ 43 ]. Three RA treatment studies with patient participants included attributes relating to how long a treatment has been in use [ 28 , 30 , 33 ]. There was variation across these studies in terms of the relative importance of this kind of attributes.…”
Section: Resultsmentioning
confidence: 99%
“…The LCL model has been applied in many settings. Some examples include preference for residential location ( Walker and Li, 2007 ), medical procedures ( Ho et al, 2020 ; Rozier et al, 2019 ), transportation mode ( El Zarwi et al, 2017 ; Hurtubia et al, 2014 ; Shen, 2009 ; Bhat, 1997 ) vehicle ownership ( Ferguson et al, 2018 ), and in the field of environmental economics ( Araghi et al, 2016 ; Beharry-Borg and Scarpa, 2010 ).…”
Section: Methodsmentioning
confidence: 99%